Outreach invitations for FIT and colonoscopy improve colorectal cancer screening rates: A randomized controlled trial in a safety‐net health system. Issue 3 (4th November 2015) - Singal, Amit G.; Gupta, Samir; Tiro, Jasmin A.; Skinner, Celette Sugg; McCallister, Katharine; Sanders, Joanne M.; Bishop, Wendy Pechero; Agrawal, Deepak; Mayorga, Christian A.; Ahn, Chul; Loewen, Adam C.; Santini, Noel O.; et al.
Abstract : BACKGROUND: The effectiveness of colorectal cancer (CRC) screening is limited by underuse, particularly among underserved populations. Among a racially diverse and socioeconomically disadvantaged cohort of patients, the authors compared the effectiveness of fecal immunochemical test (FIT) outreach and colonoscopy outreach to increase screening participation rates, compared with usual visit‐based care. METHODS: Patients aged 50 to 64 years who were not up‐to‐date with CRC screening but used primary care services in a large safety‐net health system were randomly assigned to mailed FIT outreach (2400 patients), mailed colonoscopy outreach (2400 patients), or usual care with opportunistic visit‐based screening (1199 patients). Patients who did not respond to outreach invitations within 2 weeks received follow‐up telephone reminders. The primary outcome was CRC screening completion within 12 months after randomization. RESULTS: Baseline patient characteristics across the 3 groups were similar. Using intention‐to‐screen analysis, screening participation rates were higher for FIT outreach (58.8%) and colonoscopy outreach (42.4%) than usual care (29.6%) ( P <.001 for both). Screening participation with FIT outreach was higher than that for colonoscopy outreach ( P <.001). Among responders, FIT outreach had a higher percentage of patients who responded before reminders (59.0% vs 29.7%; P <.001). Nearly one‐half of patients in the colonoscopy outreach group crossed over to complete FIT via usual care, whereas <5% of patients in the FIT outreach group underwent usual‐care colonoscopy. CONCLUSIONS: Mailed outreach invitations appear to significantly increase CRC screening rates among underserved populations. In the current study, FIT‐based outreach was found to be more effective than colonoscopy‐based outreach to increase 1‐time screening participation. Studies with longer follow‐up are needed to compare the effectiveness of outreach strategies for promoting completion of the entire screening process. Cancer 2016;122:456–463. © 2015 American Cancer Society . Abstract : In a randomized controlled trial among 5999 patients who were followed in a safety‐net health system, mailed outreach invitations appear to significantly increase colorectal cancer screening rates compared with usual care with opportunistic visit‐based screening. Fecal immunochemical test‐based outreach appears to be significantly more effective than colonoscopy‐based outreach to increase 1‐time screening participation.